Weaving Structural Violence into Trauma-Informed Qualitative Health Research with Populations Considered Vulnerable - Catherine Liao; Colleen Varcoe; Helen Brown; Ian Pike (International Journal of Qualitative Methods)
Trauma-informed approaches (TIA) are widely used in sensitive research to prevent re-traumatization and support the well-being of participants, often labelled as hard-to-reach or hidden populations . These labels reflect an individual-level framing, implying that certain groups have made themselves difficult to engage rather than acknowledging the structural barriers that limit their access to services and research participation. Trauma is deeply interconnected with social exclusion and systemic inequities. To address these limitations, researchers can further enhance trauma-informed research through a trauma- and violence-informed care (TVIC) approach, which emphasizes the structural and interpersonal violence experienced by populations considered vulnerable. A TVIC lens challenges deficit-based narratives by shifting focus away from individual responsibility and toward the structural violence that creates these conditions. This paper reflects on a qualitative study exploring burn injuries among underserved communities, particularly Indigenous Peoples and individuals experiencing homelessness or unstable housing. Burn injuries and fire-related incidents are often attributed to individual behaviour, obscuring the structural conditions that contribute to these outcomes. The paper uses researcher experiences to inform understanding of the need for trauma- and violence-informed qualitative research. Data collection involved document analysis, qualitative interviews, participant observations, and informal conversations, with the researcher using lessons learned to highlight the importance of applying a TVIC approach with populations considered vulnerable across all research stages—from researcher preparation and interview methodologies to sustained participant engagement. The lessons learned during the research underscore the need to move beyond individual-level framings of trauma to recognize structural determinants shaping lived and living experiences. A TVIC approach enhances equity-oriented research methodologies, equipping researchers to critically engage with systemic forces influencing participants’ realities. A structural perspective can help researchers develop methods, practices, and analyses that drive transformative and structurally oriented solutions.